ผลของการกร่อนเชิงชีวภาพโดยเม่นทะเลหนามดำ Diadema setosum (Leske, 1778) บนปะการังเขากวาง Acropora millepora (Ehrenberg, 1834) - นิติ วงศ์เทพวาณิชย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
Sea urchin is one of the bioeroders that can have an influence on bioerosive processes in reefs. In this study, the bioerosion on a staghorn coral Acropora millepora (Ehrenberg, 1834) by the sea urchin Diadema setosum (Leske, 1778) was investigated. Both field surveys and experiments were conducted. From the field surveys at Chon Buri Province in the upper Gulf of Thailand, the highest abundance of sea urchins (approximately 11 individuals m-2) was found at Ko Tao Mo. In addition, two experiments were conducted to investigate the interaction between sea urchins and corals and the interaction between sea urchin, corals, and algae Cladophora sp. The results of the interaction experiment without algae showed that bioerosion rate of one sea urchin was approximately 0.20 g day-1 and 1.59 cm-2 day-1 in term of CaCO3 and area respectively. The bioeorion rate in the experiment without algae was higher than that of with algae. However, there were some correlation between the densities of sea urchins, sizes of sea urchins, and the bioerosion rates. After 14 days of the experiment, if the damage by the sea urchins was less than 30% of the coral colony area, and the corals were placed in the hatchery for recovery, those corals could recover and survive 100%. On the other hand, if the corals were placed in the natural reefs for recovery, those corals could recover and survive in all damage conditions by urchins.